Investigation on Impact Behavior of Projectile Towards AHSS Target Plate at High Velocity and Hypervelocity Impact - Palanisamy, Vikneswaran; Bin Ibrahim, Mohd Norihan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study focuses on investigating the impact behavior of a projectile on an Advanced High-Strength Steel (AHSS) target plate under high-velocity and hypervelocity impact conditions. The Finite Element Method (FEM) is employed to simulate the impact event using SolidWorks and ANSYS software. The primary objective of the research is to understand the response of AHSS target plates subjected to projectile impact at high velocities. By utilizing FEM simulations, various parameters such as impact velocity, projectile material, and target plate thickness are systematically analyzed to evaluate their influence on the impact behavior and structural integrity of the AHSS plate. The study begins with a comprehensive literature review to establish a theoretical foundation for impact mechanics and the specific characteristics of AHSS materials. Subsequently, a detailed methodology for conducting FEM simulations using SolidWorks and ANSYS is presented. The FEM simulations consider the dynamic interactions between the projectile and AHSS target plate, accounting for factors such as material properties, contact behavior, and energy dissipation during impact. The results obtained from the simulations are analyzed to determine the deformation patterns, stress distribution, and damage mechanisms within the target plate. The findings of this investigation provide valuable insights into the impact behavior of AHSS target plates, enabling the development of improved designs and protective measures against high-velocity and hypervelocity impacts. The research outcomes can have significant implications for applications in areas such as aerospace, defence, and automotive industries where AHSS materials are increasingly utilized for their enhanced strength and lightweight properties.